No increased risk of mothers of children with autism having androgen-related cancers in an Australian population based sample. (October 2021) - May, T.; Vollenhoven, B.; Williams, K.
Highlights: Past research exploring a link between autism spectrum disorder and testosterone related cancers have been equivocal. This study explored self-reported breast, uterine and cervical cance. Mothers of children with and without parent-reported ASD in the population based Longitudinal Study of Australian Children were explored. No increased odds of breast, uterine and cervical cancer was found in mothers of children with ASD. Abstract: Background: Some past studies have suggested a link between autism spectrum disorder (ASD) and testosterone related cancers. This study explored androgen-related cancer in mothers of children with and without parent-reported ASD in a prospective Australian population based sample. Methods: Odds of self-reported breast, uterine and cervical cancer in mothers of children with and without parent-reported ASD in the Longitudinal Study of Australian Children. This prospective population based study contains two cohorts of children recruited at birth or 4 years of age. Results: Of 324 children with parent-reported ASD and 6, 948 without, there were no significantly increased odds for children with ASD and mother breast (AOR 1.20 [95 % CI .50, 2.87]), uterine (AOR .92 [95 % CI .05, 15.78]), cervical (AOR 1.23 [95% CI .46, 3.25]) or all cancers (AOR 1.13 [95% CI .58, 2.21]). Conclusions: This study found no evidence to support an increased or decreased androgen related cancer risk in mothers of children with parent-reported ASD.